A Single-Chip Si-Bipolar 1.6-GHz VCO with Integrated-Bias Network - Zannoth, Markus; Fenk, Josef; Springer, Andreas; Weigel, Robert (IEEE Transactions on Microwave Theory and Techniques, 2000)
A single-chip 2.7-V voltage-controlled oscillator (VCO) with an integrated-bias network has been implemented in an Si-bipolar process with an fT of 25 GHz. With an on-chip resonator consisting of vertically coupled inductors and varactor diodes, an oscillation frequency of 1.56 GHz was measured. A careful design of the oscillator and bias network was necessary to achieve a phase noise performance of -139 dBc/Hz at 4.7 h MHz off carrier. The tuning sensitivity was 100 MHz/V, which is sufficient to compensate for production tolerances. The VCO can be used as a building block for single-chip transceivers in digital European cordless telephone or global system for mobile communication systems.
elib2cris::1512001600,zennoth2000
Keywords: VCO; Si-Bipolar